Synthesis and Microstructure Properties of (Bi,Pb)2Sr2Ca1Cu2Oy Ceramic Superconductor - nurmalita .; Zuraini .; Evi Yufita; Fauzi . (Journal of Aceh Physics Society, 2015)
Properties of (Bi, Pb)2Sr2Ca1Cu2Oy ceramic superconductors were prepared by the melt textured growth methods in order to investigate the effects of the slow cooling time on the microstructur.  Phase analyses of the samples by X-ray diffraction (XRD) has been carried out to assess the effects of the slow cooling time. From XRD analyses, the addition to the sample of  the slow cooling time degrades formation of the high-Tc Bi-2212 phase. The possible reasons for the observed degradation in the microstructure properties due to the slow cooling time addition were discussed.